Anisotropic relaxations introduced by Cd impurities in rutile TiO₂: first-principles calculations and experimental support - Errico, Leonardo Antonio (2002)
We present an ab initio study of the relaxationsintroduced in TiO₂ when a Cd impurity substitutes a Ti atom and an experimental testof this calculation by a perturbed-angular-correlation (PAC) measurement ofthe orientation of the electric-field gradient (EFG) tensor at the Cd site. The ab initio calculation predicts strong anisotropicrelaxations of the nearest oxygen neighbors of the impurity and a change ofthe orientation of the largest EFG tensor component, V₃₃, from the [001] to the [110] direction upon substitution of a Ti atom by a Cd impurity.The last prediction is confirmed by the PAC experiment that shows that V₃₃ at the Cd site is parallel to either the [110] or the [110] crystal axis.